2018
DOI: 10.1044/2017_aja-17-0057
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Chinese Sound Test: Auditory Performance of Hearing Aid Users

Abstract: The results confirm the validity of the Chinese Sound Test, indicating that the testing sounds can be reliably used to assess the perception of frequency-specific information. Crucially, these data also demonstrate that the Chinese Sound Test is a useful tool to identify red flags of poor auditory access in daily environment to monitor device malfunctions and possible hearing fluctuations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…As with the Ling six sounds, the Chinese Sound Test was examined for its reliability, but instead of clinical settings, it was examined for use in daily life. The results confirmed that the Chinese Sound Test can reflect hearing thresholds, indicating its crucial role in monitoring fluctuating hearing [22].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…As with the Ling six sounds, the Chinese Sound Test was examined for its reliability, but instead of clinical settings, it was examined for use in daily life. The results confirmed that the Chinese Sound Test can reflect hearing thresholds, indicating its crucial role in monitoring fluctuating hearing [22].…”
Section: Introductionsupporting
confidence: 68%
“…Six Mandarin phonemes (/u, ɤ, a, i, tɕʰ, s/) identified as clinically important to aural rehabilitation in Hung and colleagues [ 21 , 22 ] were selected. These phonemes were selected for their frequency specificity, early age of acquisition, and intraarticulatory and inter-articulatory stability.…”
Section: Methodsmentioning
confidence: 99%
“…If a child cannot detect /u/ at 50 dB HL in a bilaterally aided condition, the audiologist would need to improve the hearing gains at low frequencies. Crucially, previous research has reported that the Chinese Sound Test can be reliably used to assess the perception of frequency-specific information and identify red flags of poor auditory access in the daily environment to monitor hearing fluctuations or device malfunctions [27]. Apart from the six phonemes of the Chinese Sound Test, we also included five other consonants /t, ɕ, tʂ, k h , and f/.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure the experiment last an appropriate length of time, only 11 Chinese phonemes, 4 vowels, and 7 consonants were used in the SDT test, as shown in Table 2. Among the testing sounds, we first selected the 6 phonemes /u, ə, a, i, tɕʰ, and s/ from the Chinese Sound Test because of their clinical relevance in aural habilitation or rehabilitation [9, 27]. The six phonemes ranged from low-to-high frequencies across the Chinese speech spectrum and were commonly used in audiometry tests or aural habilitation sessions to quickly screen a child’s auditory performance.…”
Section: Methodsmentioning
confidence: 99%
“…Diagnoza audiologiczna powinna być uzupełniona odpowiednio przygotowanymi i sprawdzonymi badaniami ankietowymi. Do tej pory baza kwestionariuszy przeznaczonych do oceny rozwoju słuchowego po zastosowaniu aparatów/implantów słuchowych u małych dzieci pozostaje bardzo ograniczona [8][9]. Narzędziem, które opracowano w języku polskim i które służy do oceny rozwoju słuchowego oraz skuteczności przeprowadzonej interwencji medycznej u dzieci poniżej 24. miesiąca życia, jest kwestionariusz LittlEARS (LittlEARS Auditory Questionnaire) [10].…”
Section: Wstępunclassified